2003
DOI: 10.1088/0957-4484/14/5/310
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of CuAlO2nanocrystalline transparent thin films with high conductivity

Abstract: P-type transparent CuAlO2 semiconductor films are made by the spin-on technique from nanocrystals. The nanocrystals are synthesized by a hydrothermal metathesis reaction. Scanning electron microscopy, x-ray diffraction and energy dispersive x-ray spectrometry suggest that the films contain nanocrystalline phases of CuAlO2. Both the Hall technique and Seebeck measurements reveal that the film is p-type and a very high room-temperature conductivity of 2.4S cm−1 is achieved. This success in fabricating a high-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 18 publications
2
46
0
Order By: Relevance
“…It gives rise to some very interesting and useful properties which are exploited in many commercial devices, but this depends on the method of material preparation and post processing treatments. Recently Gao et.al [3] observed the enhancement of electrical conductivity from 1 S/cm to 2.4 S/cm when the crystallite size was reduced to nanodimension. Techniques like pulsed laser deposition [2], ion exchange reaction [3] and sputtering [4] were widely used to synthesis single phase CuAlO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It gives rise to some very interesting and useful properties which are exploited in many commercial devices, but this depends on the method of material preparation and post processing treatments. Recently Gao et.al [3] observed the enhancement of electrical conductivity from 1 S/cm to 2.4 S/cm when the crystallite size was reduced to nanodimension. Techniques like pulsed laser deposition [2], ion exchange reaction [3] and sputtering [4] were widely used to synthesis single phase CuAlO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently Gao et.al [3] observed the enhancement of electrical conductivity from 1 S/cm to 2.4 S/cm when the crystallite size was reduced to nanodimension. Techniques like pulsed laser deposition [2], ion exchange reaction [3] and sputtering [4] were widely used to synthesis single phase CuAlO 2 . Recently the author reported the synthesis of nanocrystalline CuAlO 2 by mechanical alloying process using Cu 2 O and α-Al 2 O 3 powders, the grain and grain boundary contribution electrical conductivities [5] and the existence of Debye type dielectric relaxation behaviour [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been many works on the production and investigation of the physical properties of transparent conducting oxide (TCO) materials due to their electrical and optical properties such as low resistivity and high optical transmittance [15]. The rst report of a TCO was published in 1907, when Badeker reported that thin lms of Cd metal deposited in a glow discharge chamber could be oxidized to become transparent while remaining electrically conducting [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thin lms of n-type transparent conducting oxides (n-TCOs) such as zinc oxide (ZnO) [8], cadmium oxide (CdO) [911], indium oxide (In 2 O 3 ) [12], tin oxide (SnO 2 ) [13], indium tin oxide (ITO) [14] and p-type transparent conducting oxides (p-TCOs) such as CuAlO 2 [15,16], SrCu 2 O 2 [17], tin gallium oxide [18], etc. have received considerable attention mainly due to their important potential applications, which include photovoltaic solar cells, gas sensors, transparent electrodes, and other optoelectronic devices [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation